URGENSI NILAI-NILAI AGAMA ISLAM DALAM PENDIDIKAN ANAK DI ERA DIGITAL - Wirman Hanizon (El-Rusyd, 2023)
Globally, fundamental changes as a result of the digital age. Not only in the field of technology and communication, changes also occur in children's daily behavior. Various bad shows can be accessed by children easily and can have negative behavioral effects on children. Supervision from parents is needed to guide children so that negative impacts can be minimized. The problem that occurs is that most parents are confused about what should be done to prepare children to face their environment. Instilling religious values from an early age is expected to be one of the bulwarks of children facing change. This study aims to describe the early cultivation of religious values in the digital age which is full of extraordinary challenges through several strategies for instilling religious values such as understanding parental responsibility, parental commitment to children, and learning from the noblest example in Islam. The results of this study are expected to be one of the inputs for the world of children's education, especially in the family environment in preparing children in the digital era which is also referred to as the era of disruption.